Coal-based porous carbon, preparation method and application thereof
Patent Information
- Application Number
- CN202610922129.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-25
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2046-06-25
AI Technical Summary
但是,但现有技术尚未形成一套可稳定制备高孔容、高比表面积、低灰分的CVD用煤基多孔炭的方法
本发明通过同时控制活化温度、活化时间、水蒸气流量及长焰煤粒径,利用活化温度、活化时间、水蒸气流量以及长焰煤粒径之间的配合,从“单变量控制”升级为“多参数协同优化”,可以获得具有高孔容、高比表面积、低灰分的煤基多孔炭,将其用于CVD硅碳负极,能显著提高硅负极的循环稳定性和首次库仑效率。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of secondary battery materials technology, and in particular to a coal-based porous carbon, its preparation method, and its application. Background Technology
[0002] Currently, the preparation methods for coal-based porous carbon mainly include two categories: chemical activation and physical activation. Chemical activation, using alkaline substances such as KOH and NaOH as activators, can achieve a high specific surface area, but it suffers from problems such as equipment corrosion, environmental pollution, and high costs. Furthermore, the reaction system during alkaline activation is highly corrosive, easily damaging the furnace and pipelines. Additionally, repeated washing with strong acid after activation is required to remove residual salts, generating large amounts of saline waste liquid, which burdens the environment and incurs high treatment costs. Simultaneously, chemical activation introduces exogenous metal ions, leading to increased ash content and magnetic impurities in the product, which is detrimental to obtaining high-purity porous carbon materials.
[0003] In contrast, steam activation is a clean physical activation process. This method uses steam as the sole activation medium, reacting it with carbon at high temperatures (C + H₂O → CO + H₂) to etch the carbon framework and form a porous structure. This method requires no chemical activators, produces corrosion-free equipment and no acid or alkaline wastewater emissions, and the byproduct gases are combustible and recyclable. The process is simple, environmentally friendly, and suitable for continuous production. Furthermore, steam activation does not introduce metallic impurities, producing low-ash, high-purity coal-based porous carbon, making it an ideal route for green production. Existing steam activation processes primarily serve the adsorption field, producing products with low pore volume and limited specific surface area, which cannot meet the requirements of CVD (Chemical Vapor Deposition) silicon-carbon anode materials.
[0004] CVD coal-based porous carbon serves as the framework material for silicon-carbon anodes in the construction of high-performance lithium-ion batteries. This coal-based porous carbon needs to meet the characteristics of high pore volume, high specific surface area, and low ash content. However, current technology has not yet developed a stable method for preparing CVD coal-based porous carbon with high pore volume, high specific surface area, and low ash content. Summary of the Invention
[0005] In order to overcome the above-mentioned defects and deficiencies in the existing technology, the present invention aims to provide a coal-based porous carbon, its preparation method and its application.
[0006] One objective of this invention is to provide a method for preparing coal-based porous carbon, comprising: Provide carbonized feedstock, which is obtained by carbonizing long-flame coal, and, Coal-based porous carbon is obtained by activating the carbonized material with steam. The particle size of the long-flame coal is 30μm≤D50≤2000μm; The activation satisfies the following process parameters: The activation temperature is 750~1050℃, the activation time is 1~8h, and the steam flow rate is 60~140L / min; The activation temperature, activation time, steam flow rate, and particle size of the long-flame coal satisfy the following relationship: The co-activation index Z is defined as follows:
[0007] Where A is the activation temperature in °C, B is the activation time in h, C is the steam flow rate in L / min, and D50 is the particle size of the long-flame coal in μm; Z satisfies: 0 ≤ Z ≤ 4.
[0008] Preferably, Z satisfies: 0.73≤Z≤2.04.
[0009] Preferably, the activation temperature is 850~1000℃, and / or, The activation time is 2-4 hours, and / or, The steam flow rate is 80~120 L / min, and / or, The particle size of the long-flame coal is 800μm≤D50≤1500μm.
[0010] Preferably, the activation temperature is 900~1000℃.
[0011] Preferably, the activation is carried out in a water vapor atmosphere.
[0012] Preferably, the process further includes: acid washing, water washing, and drying of the activated product to obtain coal-based porous carbon.
[0013] The second objective of this invention is to provide a coal-based porous carbon, which is prepared by the method described above.
[0014] Preferably, the coal-based porous carbon satisfies at least one of the following characteristics: Specific surface area: 1200–3000 m² / g; Pore volume: 0.6–1.4 cm³ / g; Ash content ≤0.2 wt.%; Compacted density: 0.35~0.55 g / cm³; and, Impurity metal content (Fe, K, Na) ≤ 500 ppm.
[0015] A third objective of this invention is to provide an application of the coal-based porous carbon described above in lithium-ion batteries.
[0016] The beneficial effects of this invention are: This invention, by simultaneously controlling activation temperature, activation time, steam flow rate, and long-flame coal particle size, and utilizing the coordination among activation temperature, activation time, steam flow rate, and long-flame coal particle size, upgrades from "single-variable control" to "multi-parameter synergistic optimization," which can obtain coal-based porous carbon with high pore volume, high specific surface area, and low ash content. When used in CVD silicon-carbon anodes, it can significantly improve the cycle stability and first coulombic efficiency of silicon anodes.
[0017] Furthermore, by introducing the particle size D50 of long-flame coal into the synergistic control system of the activation process, the activation reaction is transformed from simply adjusting the reaction intensity into a structure-oriented construction process that takes into account diffusion path, gasification rate and framework preservation, thereby obtaining coal-based porous carbon that is more suitable for CVD silicon deposition. Detailed Implementation
[0018] The present invention will be further described in detail below with reference to embodiments. The specific embodiments described herein are only for explaining the related invention and are not intended to limit the invention. Unless otherwise specified, the embodiments and features in the embodiments of the present invention can be combined with each other. The present invention will be described in detail below with reference to embodiments.
[0019] Unless otherwise specified, the materials, reagents, and apparatus used in the following examples can be obtained commercially or prepared according to methods published in the literature.
[0020] In this document, when values are described as ranges, it should be understood that such disclosure includes disclosure of all possible subranges within that range, as well as the specific numerical values falling within that range, regardless of whether the specific numerical value or specific subrange is explicitly specified.
[0021] In this invention, the specific surface area and pore size distribution are measured by nitrogen adsorption, and the impurity content is measured by ICP or ash content testing.
[0022] Existing activation processes lack systematic optimization of activation temperature, activation time, and water vapor flow rate, easily leading to uneven pore structure development, poor pore connectivity, or excessive erosion of the framework. Furthermore, the activated material has high ash content and magnetic impurity content, resulting in insufficient purity and making it difficult to use directly in battery systems. The inventors of this invention discovered that by simultaneously controlling activation temperature, activation time, water vapor flow rate, and long-flame coal particle size, and utilizing the coordination between these parameters, a shift from "single-variable control" to "multi-parameter synergistic optimization" can be achieved. This allows for the production of coal-based porous carbon with high pore volume, high specific surface area, and low ash content. When used in CVD silicon-carbon anodes, this significantly improves the cycle stability and initial coulombic efficiency of silicon anodes, thus completing this invention.
[0023] According to one aspect of the present invention, a method for preparing coal-based porous carbon is provided, comprising: Provide carbonized feedstock, which is obtained by carbonizing long-flame coal, and, Coal-based porous carbon is obtained by activating the carbonized material with steam. The particle size of the long-flame coal is 30μm≤D50≤2000μm; The activation satisfies the following process parameters: The activation temperature is 750~1050℃, the activation time is 1~8h, and the steam flow rate is 60~140L / min; The activation temperature, activation time, steam flow rate, and particle size of the long-flame coal satisfy the following relationship:
[0024] Where A is the activation temperature (°C), B is the activation time (h), C is the steam flow rate (L / min), and D50 is the particle size of the long-flame coal (μm). Extensive process screening and performance testing revealed that when the synergistic activation index Z satisfies: With 0≤Z≤4, the resulting coal-based porous carbon can achieve comprehensive optimization of pore structure and mechanical strength.
[0025] It should be noted that simply controlling the activation temperature, activation time, steam flow rate, and long-flame coal particle size within the aforementioned ranges does not guarantee the acquisition of coal-based porous carbon with superior structure and performance. When the synergistic activation index Z calculated according to the above formula is less than 0, it often indicates that the activation system is generally "mild," such as a low temperature, short activation time, and / or insufficient steam flow rate. In this case, the carbon material is not sufficiently activated, the pores are mainly concentrated in a small number of micropores, the proportion of small mesopores of 1–3 nm is low, the specific surface area and pore volume are at or below the lower limit of the range, and the compaction density is high. This results in insufficient silicon deposition space and poor electrolyte wettability, which is not conducive to the subsequent construction of high-load silicon-carbon anodes.
[0026] Conversely, when all four parameters are within the allowable range, but the calculated Z is greater than 4, it indicates that the activation combination conditions are generally "harsh". For example, the temperature is too high, the time is too long, and / or the water vapor flow rate is too large. This can easily cause excessive etching of the framework carbon, resulting in thinning of the pore walls or even framework fracture. The direction of the radial large pores and through pores may shift. Although the specific surface area and pore volume may continue to increase, the proportion of effective 1-3 nm pores decreases. The ash content is difficult to effectively support the framework, the compaction density decreases significantly, and the mechanical strength of the material is insufficient. Powdering and pore structure collapse are likely to occur during electrode pressing and cycling.
[0027] Therefore, based on the limitations of activation temperature (750–1050 °C), activation time (1–8 h), steam flow rate (60–140 L / min), and long-flame coal D50 particle size (30–2000 μm), this invention further uses the synergistic activation index Z as a comprehensive criterion, requiring Z to be controlled between 0 and 4. Compared with constraining only a single process parameter, when the Z condition is met simultaneously, the matching relationship between the four process parameters is more reasonable. The resulting coal-based porous carbon not only has a specific surface area of 1200–3000 m² / g and a pore volume of 0.6–1.4 cm³ / g, but also has a high proportion of 1–3 nm pore sizes, a stable compaction density in the range of 0.35–0.55 g / cm³, good pore structure connectivity and framework strength, and significantly improved batch-to-batch consistency, making it more suitable as a porous carbon framework material for silicon-carbon composite anodes.
[0028] In this invention, activation temperature, activation time, steam flow rate, and long-flame coal particle size are coordinated to solve the technical problem to be addressed, as detailed below: In this invention, the long-flame coal-based precursor of the carbonized material provides a carbon skeleton structure and serves as a carrier for pore formation. After carbonization, it retains a moderate amount of amorphous carbon and aromatic interlayer carbon, providing active sites for subsequent activation reactions.
[0029] D50, also known as median particle size, represents the characteristic particle size at which the cumulative distribution percentage in a particle group reaches 50%. D50 has a well-known meaning in the art and can be determined using instruments and methods known in the art. For example, it can be determined using laser diffraction, and can be measured using a laser diffraction scattering intensity distribution measuring device.
[0030] In this invention, the long-flame coal refers to high-volatile, low-rank coal with a vitrinite maximum reflectance R between 0.50% and 0.65%. The long-flame coal has a particle size of 30 μm ≤ D50 ≤ 2000 μm, with exemplary D50 values of 30 μm, 50 μm, 200 μm, 500 μm, 800 μm, 1000 μm, 1500 μm, 1800 μm, or 2000 μm. A D50 ≤ 2000 μm improves gas diffusion paths and controls reaction rates, effectively avoiding surface over-etching and internal under-etching, forming a self-regulating activation mechanism of hierarchical pore structure, promoting pore connectivity and mesopore formation, ensuring uniform pore structure development, and achieving a through-type micro-mesoporous composite structure. If D50 is less than 30 μm, the long-flame coal will be blown away in the activation equipment (e.g., a rotary kiln), causing some of the long-flame coal to fail to undergo normal activation, reducing the yield.
[0031] Furthermore, this invention uses long-flame coal as the carbon source, which balances low ash content and high reactivity, thus improving the uniformity of the pore structure. In addition, this invention transforms low-rank long-flame coal from a traditional fuel into a high-performance battery-grade functional carbon material, realizing the transformation of coal resource utilization from "energy-oriented" to "material-oriented," increasing resource added value and utilization efficiency, and providing a new path for the green transformation of the coal chemical industry.
[0032] In this invention, the activation reaction is a gasification reaction, using steam as the sole activation medium and the main oxidant, replacing the alkaline chemical activation system. Pore formation is achieved through a purely physical gasification reaction (C + H₂O → CO + H₂), without the involvement of chemical reagents. The process is non-corrosive, produces no waste liquid, and has a long equipment lifespan, representing a green and clean production route. The generated gases, H₂ and CO, are combustible and recyclable, achieving clean closed-loop production. Compared to traditional alkaline activation processes, this invention offers significant advantages in technical performance, environmental friendliness, cost control, and industrial application value. Furthermore, steam activation eliminates the need for expensive chemical reagents, utilizes widely available and inexpensive activators, and requires only simple water washing after activation, reducing acid consumption and significantly decreasing water and energy consumption. Overall, the unit product cost is reduced by approximately 40%–50% compared to alkaline activation processes, and the equipment maintenance cycle is extended by 3–5 times, demonstrating significant economic benefits. In addition, the alkaline vapor in traditional alkaline activation is prone to corroding key components such as quartz furnace tubes and heating elements. However, this invention uses a neutral water vapor atmosphere, which ensures stable long-term operation and extends the equipment life to more than 5,000 hours. It is suitable for continuous production of various types of industrial equipment such as tube furnaces, pusher furnaces, and rotary furnaces.
[0033] During the activation process, water vapor enters the pores of the carbonized material and reacts with the surface active carbon atoms to generate CO and H2. The slight positive pressure of the generated gas promotes the further penetration of water vapor into the interior, allowing the reaction to proceed layer by layer. As the reaction proceeds, micropores are continuously generated and interconnected to form mesopores. The particle size of the carbonized material and the water vapor flow rate together determine the pore connectivity. The presence of H2 has a mild reduction and rearrangement effect on the carbon skeleton surface, making the pore walls dense and the structure stable.
[0034] In this invention, the steam flow rate is controlled between 60 and 140 L / min. This steam flow rate limit is based on the following conditions: the activation equipment is a rotary kiln, the feed rate is 6 kg, and the steam flow rate at this time is 60–140 L / min. In other words, the steam flow rate in this embodiment of the invention is the actual flow rate under the conditions of a rotary kiln and a single feed rate of 6 kg. For different equipment specifications or processing capacities, the flow rate can be adjusted proportionally.
[0035] Exemplary steam flow rates are 65 L / min, 70 L / min, 75 L / min, 80 L / min, 85 L / min, 90 L / min, 95 L / min, 100 L / min, 105 L / min, 110 L / min, 115 L / min, 120 L / min, 125 L / min, 130 L / min, 135 L / min, or 140 L / min. Controlling the steam flow rate to 60~140 L / min adjusts the vaporization rate. The H2 generated from the decomposition of steam can mildly reduce the carbon surface, inhibiting excessive etching and achieving gentle activation. If the steam flow rate is less than 60 L / min, the partial pressure of steam supply will be insufficient, the gasification reaction (C-H2O) rate will be low, and the activation driving force will be insufficient, which will easily lead to the following problems: insufficient pore development (low specific surface area and pore volume), "wasted" effective activation time (insufficient activation degree in the same amount of time), pore structure will not be easy to open and batch stability will deteriorate. If the steam flow rate is greater than 140 L / min, it may lead to increased loss of fine particles, affecting the yield and activation stability.
[0036] In a preferred embodiment of the present invention, a controllable steam delivery system (flow control accuracy ≤ ±5L / min) is used to ensure a stable reaction rate.
[0037] In this invention, the activation temperature controls the vaporization rate, and the activation time controls the pore volume development. The activation temperature is 750~1050℃, with exemplary activation temperatures being 750℃, 780℃, 820℃, 850℃, 860℃, 880℃, 900℃, 930℃, 950℃, 980℃, 1000℃, or 1050℃. At an activation temperature of 750℃, the reaction rate is relatively low, and the pore volume begins to increase; at an activation temperature of 850℃, the reaction rate is still relatively low, and pore structure development is limited; at an activation temperature of 900℃, the reaction rate increases, and both the specific surface area and pore volume increase; at an activation temperature of 950℃, the reaction rate accelerates, and the pore diameter becomes larger; at an activation temperature of 1050℃, the reaction rate significantly accelerates, and both the pore volume and specific surface area significantly increase.
[0038] In this invention, if the activation temperature is less than 750°C, the gasification reaction is insufficient; if the activation temperature is greater than 1050°C, pore collapse is likely to occur.
[0039] In this invention, the activation time is 1 to 8 hours, with exemplary activation times being 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours, 6 hours, 6.5 hours, 7 hours, 7.5 hours, or 8 hours. If the activation time is less than 1 hour, the required specific surface area and pore volume cannot be achieved; if the activation time is greater than 8 hours, the yield will be significantly lower, and the pore size will be significantly larger.
[0040] In this invention, activation temperature and activation time work together to determine the micropore-to-mesopore ratio and the integrity of the framework. By matching the activation temperature and time, a synergistic distribution of 1-3 nm micropores and mesopores can be achieved, resulting in a concentrated pore size distribution and strong connectivity, which is suitable for the gas transport requirements in the CVD silicon deposition process.
[0041] The method described in this invention is a typical but non-limiting adaptation to the continuous operating system of rotary kilns and is feasible for large-scale implementation.
[0042] The coal-based porous carbon of the present invention can satisfy at least one of the following characteristics: High specific surface area (1200~3000 m² / g); High pore volume (0.6–1.4 cm³ / g); Low ash content (≤0.2 wt.%); Compacted density: 0.35~0.55 g / cm³; and, Impurity metal content (Fe, K, Na): ≤500 ppm.
[0043] The final sample of the coal-based porous carbon of the present invention has a pore size mainly distributed in the range of 1~3 nm, forming a hierarchical pore network, which has excellent gas diffusion ability and Si deposition carrying capacity.
[0044] Coal-based porous carbon that meets the above characteristics can be directly used as the carbon skeleton of CVD silicon-carbon composite anode. When used in lithium-ion batteries, it can significantly improve the uniformity and adhesion of silicon deposition. The resulting Si / C composite anode has a specific capacity of ≥1100mAh / g, an initial coulombic efficiency of ≥88%, and a cycle life of over 1000 cycles. The material has a stable structure and excellent conductivity, and has the potential for industrial application.
[0045] Preferably, Z satisfies: 0.73≤Z≤2.04, which can significantly improve the first coulombic efficiency of silicon-carbon composite anode.
[0046] In a preferred embodiment of the present invention, the activation temperature is 850~1000℃, and / or the activation time is 2~4h, and / or the steam flow rate is 80~120L / min, and / or the particle size of the long-flame coal is 800μm≤D50≤1500μm.
[0047] In a preferred embodiment of the present invention, the activation temperature is 900~1000℃.
[0048] In this invention, the method for carbonizing long-flame coal is not particularly limited. As a typical but non-limiting embodiment, the carbonization includes: heating the dried long-flame coal in a nitrogen atmosphere at a heating rate of 4-6℃ / min, and holding it at 300-400℃, 500-600℃, and 750-850℃ for 30min each, to obtain carbonized material. Further, the carbonization includes: placing the dried long-flame coal in a quartz boat and heating it in a nitrogen atmosphere (flow rate of 100mL / min) at a heating rate of 5℃ / min, and holding it at 350℃, 550℃, and 800℃ for 30min each, to obtain carbonized material.
[0049] In a preferred embodiment of the present invention, the carbonized sample should be kept in block or granular form to ensure uniform gas diffusion during the activation stage.
[0050] In a preferred embodiment of the present invention, the activation is carried out in a water vapor atmosphere.
[0051] In a preferred embodiment of the present invention, the activation is carried out in a rotary kiln.
[0052] In a preferred embodiment of the present invention, the method further includes: acid washing, water washing, and drying of the activated product to obtain coal-based porous carbon. An exemplary acid washing method is acid washing with dilute hydrochloric acid, and an exemplary water washing method is washing with deionized water until the pH reaches 6-7.
[0053] According to another aspect of the present invention, a coal-based porous carbon is provided, which is prepared by the method described above.
[0054] The coal-based porous carbon of the present invention can satisfy at least one of the following characteristics: High specific surface area (1200~3000 m² / g); High pore volume (0.6–1.4 cm³ / g); Low ash content (≤0.2 wt.%); Compacted density: 0.35~0.55 g / cm³; and, Impurity metal content (Fe, K, Na): ≤500 ppm.
[0055] The final coal-based porous carbon sample of the present invention is mainly composed of micropores (1–3 nm), forming a hierarchical pore network, which has excellent gas diffusion ability and Si deposition carrying capacity.
[0056] According to another aspect of the present invention, an application of the coal-based porous carbon described above in a lithium-ion battery is provided. The lithium battery possesses all the features and advantages of the coal-based porous carbon described above, which will not be repeated here.
[0057] The coal-based porous carbon can also be used in fields such as supercapacitor electrodes, lithium-sulfur battery carriers, gas adsorption and hydrogen storage materials.
[0058] Example 1 S1: Material Selection Long-flame coal was selected as raw material, crushed and screened to a D50 of 1000 μm.
[0059] S2: Carbonization treatment The dried long-flame coal was placed in a quartz boat and carbonized under a nitrogen atmosphere (flow rate 100 mL / min) at a heating rate of 5 °C / min. The carbonized material was then held at 350 °C, 550 °C, and 800 °C for 30 min each, yielding the carbonized material. The carbonized sample should remain in block or granular form to ensure uniform gas diffusion during the activation stage.
[0060] S3: Water vapor activation The carbonized material is transferred to a rotary kiln and heated to the set activation temperature of 950℃ under steam protection. Once the kiln temperature stabilizes, steam is introduced at a flow rate of 100L / min to initiate the activation reaction. The activation time is set to 4 hours.
[0061] S4: Cooling and Washing After activation, the steam flow was stopped, and nitrogen gas was introduced to cool the sample to room temperature. The sample was washed with dilute hydrochloric acid (5 wt.%) to remove inorganic residues, then rinsed with deionized water until pH=6-7, and dried at 80℃ for 6 h to obtain coal-based porous carbon material.
[0062] Example 2 The activation temperature, activation time, steam flow rate, and particle size of the long-flame coal in Example 1 were changed, while the remaining preparation steps and methods were the same as in Example 1. In Example 2, the activation temperature was 750℃, the activation time was 1h, the steam flow rate was 60L / min, and the particle size D50 of the long-flame coal was 2000 μm.
[0063] Example 3 The activation temperature, activation time, steam flow rate, and particle size of the long-flame coal in Example 1 were changed, while the remaining preparation steps and methods were the same as in Example 1. In Example 3, the activation temperature was 1050℃, the activation time was 8h, the steam flow rate was 140L / min, and the particle size D50 of the long-flame coal was 30 μm.
[0064] Example 4 The activation temperature, activation time, steam flow rate, and particle size of the long-flame coal in Example 1 were changed, while the remaining preparation steps and methods were the same as in Example 1. In Example 4, the activation temperature was 800℃, the activation time was 4h, the steam flow rate was 100L / min, and the particle size D50 of the long-flame coal was 1000μm.
[0065] Example 5 The activation temperature, activation time, steam flow rate, and particle size of the long-flame coal in Example 1 were changed, while the remaining preparation steps and methods were the same as in Example 1. In Example 5, the activation temperature was 820℃, the activation time was 2.5h, the steam flow rate was 80L / min, and the particle size D50 of the long-flame coal was 1000 μm.
[0066] Example 6 The activation temperature, activation time, steam flow rate, and particle size of the long-flame coal in Example 1 were changed, while the remaining preparation steps and methods were the same as in Example 1. In Example 6, the activation temperature was 1000℃, the activation time was 4h, the steam flow rate was 120L / min, and the particle size D50 of the long-flame coal was 800μm.
[0067] Comparative Example 1 The activation temperature in Example 1 was changed to 600°C, and the remaining preparation steps and methods were the same as in Example 1.
[0068] Comparative Example 2 The activation temperature in Example 1 was changed to 1100℃, and the remaining preparation steps and methods were the same as in Example 1.
[0069] Comparative Example 3 The activation time in Example 1 was changed to 0.5 h, and the remaining preparation steps and methods were the same as in Example 1.
[0070] Comparative Example 4 The activation time in Example 1 was changed to 9 hours, and the remaining preparation steps and methods were the same as in Example 1.
[0071] Comparative Example 5 The steam flow rate in Example 1 was changed to 50 L / min, and the remaining preparation steps and methods were the same as in Example 1.
[0072] Comparative Example 6 The steam flow rate in Example 1 was changed to 160 L / min, and the remaining preparation steps and methods were the same as in Example 1.
[0073] Comparative Example 7 The particle size of the long-flame coal in Example 1 was changed to 20 μm, and the remaining preparation steps and methods were the same as in Example 1.
[0074] Comparative Example 8 The particle size of the long-flame coal in Example 1 was changed to 2500 μm, and the remaining preparation steps and methods were the same as in Example 1.
[0075] Comparative Example 9 A method for preparing lignite-based activated coke by steam activation, comprising the following steps: A mixture containing 22.5% asphalt (particle size <100 mesh after crushing) and 77.5% lignite (dry basis ash content <5%, moisture content <10%, particle size <100 mesh after crushing) (the percentages are the mass ratios of asphalt and lignite in the mixture) is thoroughly crushed and mixed in a crusher for 20 seconds. The mixture is then molded into shape, and the formed blocks (strips) are placed in a muffle furnace and carbonized at 600°C for 1.5 hours under anaerobic conditions. The carbonized material is then removed and crushed into blocks, placed in a pit furnace, heated to 800°C under nitrogen protection, and continuously purged with steam at a flow rate of 780 L / h for 30 minutes for steam activation. The activated material is then cooled to room temperature under nitrogen protection and removed. The resulting activated material is the prepared lignite-based activated coke.
[0076] Comparative Example 10 10-20 mesh semi-coke particles obtained by crushing and screening were thoroughly impregnated with potassium carbonate powder at a mass ratio of 0.2 for 12 hours, and then dried at 120℃ for 4 hours. The pretreated particles were then fed into an activation furnace and heated to 800℃ at a heating rate of 10℃ / min under nitrogen protection. Activation was then performed for 1 hour at an activation temperature of 800℃ and a steam mass ratio of 1.2. After cooling to room temperature, the activated carbon product was obtained by acid washing with dilute hydrochloric acid and then drying.
[0077] Performance testing The porous carbon obtained in the examples and comparative examples was subjected to performance tests, including: Specific surface area test method: GB / T 19587-2017; Aperture testing method: GB / T 19587-2017; Pore volume test method: GB / T 19587-2017; Ash content test method: GB / T 30372-2014.
[0078] The porous carbon obtained in the examples and comparative examples was used to prepare silicon-carbon composite anode materials by CVD silicon deposition, and then the electrochemical performance was tested.
[0079] Performance test results include: Table 1
Claims
1. A method for preparing coal-based porous carbon for CVD silicon-carbon anodes, characterized in that, include: Provide carbonized feedstock, which is obtained by carbonizing long-flame coal, and, Coal-based porous carbon is obtained by activating the carbonized material with steam. The particle size of the long-flame coal is 800μm≤D50≤1500μm; The carbonization process includes: heating and carbonizing dried long-flame coal in a nitrogen atmosphere at a heating rate of 4-6℃ / min, and holding it at 300-400℃, 500-600℃, and 750-850℃ for 30 minutes each to obtain carbonized material. The activation satisfies the following process parameters: The activation temperature is 850~1000℃, the activation time is 2~4h, and the steam flow rate is 80~120L / min; The activation temperature, activation time, steam flow rate, and particle size of the long-flame coal satisfy the following relationship: The co-activation index Z is defined as follows: Where A is the activation temperature in °C, B is the activation time in h, C is the steam flow rate in L / min, and D50 is the particle size of the long-flame coal in μm; Z satisfies: 0.73≤Z≤2.
04.
2. The method as described in claim 1, characterized in that, The activation temperature is 900~1000℃.
3. The method as described in claim 1, characterized in that, The activation was carried out in a water vapor atmosphere.
4. The method as described in claim 1, characterized in that, Also includes: The activated product is acid-washed, water-washed, and dried to obtain coal-based porous carbon.
5. A coal-based porous carbon, characterized in that, It is prepared by the method described in any one of claims 1-4; The coal-based porous carbon satisfies the following characteristics: Specific surface area: 1200–3000 m² / g; Pore volume: 0.6–1.4 cm³ / g; Ash content ≤0.2 wt.%; Compacted density: 0.35~0.55 g / cm³; and, Impurity metal content ≤500 ppm.
6. The application of the coal-based porous carbon as described in claim 5 in lithium-ion batteries.
Citation Information
Patent Citations
Method for preparing meso-macroporous activated carbon from long flame coal
CN109179404A
Preparation method and application of coal-based hard carbon negative electrode material
CN119683603A